EQUATION OF STATE, STRUCTURAL BEHAVIOUR AND PHASE DIAGRAM OF SYNTHETIC MGFE2O4, AS A FUNCTION OF PRESSURE AND TEMPERATURE - Levy D.; Diella V.; Dapiaggi M.; Sani A.; Gemmi M.; Pavese A. (My University, 2004)
The behaviour of synthetic Mg-ferrite (MgFe2O4) has been investigated at high pressure (in situ high-pressure synchrotron radiation powder diffraction at ESRF) and at high temperature (in situ high-temperature X-ray powder diffraction) conditions. The elastic properties determined by the third-order Birch-Murnaghan equation of state result in K0=181.5(± 1.3) GPa, K'=6.32(± 0.14) and K''= -0.0638 GPa-1. The symmetry-independent coordinate of oxygen does not show significant sensitivity to pressure, and the structure shrinking is mainly attributable to the shortening of the cell edge (homogeneous strain). The lattice parameter thermal expansion is described by αa0+αa1*(T-298)+αa2/(T-298)2, where αa0=9.1(1) 10-6 K-1, αa1=4.9(2) 10-9 K-2 and αa2= 5.1(5) 10-2 K. The high-temperature cation-ordering reaction which MgFe-spinel undergoes has been interpreted by the O'Neill model, whose parameters are α= 22.2(± 1.8) kJ mol-1 and β=-17.6(± 1.2) kJ mol-1. The elastic and thermal properties measured have then been used to model the phase diagram of MgFe2O4, which shows that the high-pressure transition from spinel to orthorombic CaMn2O4-like structure at T < 1700 K is preceded by a decomposition into MgO and Fe2O3.
Keywords: MGFE2O4; BEHAVIOUR AS A FUNCTION OF P AND T; PHASE DIAGRAM